2011
DOI: 10.2169/internalmedicine.50.5800
|View full text |Cite
|
Sign up to set email alerts
|

Combined Legionella and Escherichia Coli Lung Infection after a Tsunami Disaster

Abstract: Pulmonary infection after a tsunami is often polymicrobial and tends to form chronic pyogenic lung disease, necrotizing pneumonia, and empyemas. We report a combined pulmonary infection of Legionella and multiple antibiotic-resistant Escherichia coli in a previously well 75-year-old woman following immersion in tsunami waters 1 km inland from the Pacific coastline following the Tohoku Region Pacific Coast Earthquake of 2011. She needed drainage several times and the long-term use of multiple antibiotics accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Tsunami-related aspiration pneumonia is common among tsunami victims (Allworth 2005;Chierakul et al 2005;Ebisawa et al 2011). People who survive the wave frequently aspirate not only water, but also solid and particulate matter.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Tsunami-related aspiration pneumonia is common among tsunami victims (Allworth 2005;Chierakul et al 2005;Ebisawa et al 2011). People who survive the wave frequently aspirate not only water, but also solid and particulate matter.…”
Section: Discussionmentioning
confidence: 99%
“…People who survive the wave frequently aspirate not only water, but also solid and particulate matter. Pneumonia after the aspiration of water or after near-drowning is often polymicrobial, with causative agents including aeromonads, pseudomonads, streptococci, E. coli, and others (Kao et al 2005;Maegele et al 2006;Ebisawa et al 2011). In the patient discussed here, polymicrobial infection was supposed, but only E. coli was isolated from sputum culture and BAL fluid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Elderly evacuees under unfavorable circumstances have an increased risk for developing pneumonia, and those who aspirate a small amount of the organism may develop legionellosis. Ebisawa et al 11 have reported pulmonary co-infection of Legionella and multiple antibiotic-resistant Escherichia coli in a previously healthy 75-year-old woman, as a result of immersion in tsunami waters 1 km inland from the Pacific coastline following the 2011 Great East Japan Earthquake. This patient required drainage several times and long-term use of multiple antibiotics according to the bacteria observed and an antibiotic susceptibility test.…”
Section: Respiratory Tract Infectionmentioning
confidence: 99%